2015
DOI: 10.1016/j.jash.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of plasma renin activity and aldosterone concentration with ambulatory blood pressure responses to nebivolol and valsartan, alone and in combination, in hypertension

Abstract: After demonstration of the antihypertensive efficacy of the combination of the beta-blocker nebivolol and the angiotensin receptor blocker valsartan in an 8-week, randomized, placebo-controlled trial (N = 4161), we now report the effects of this treatment on the renin-angiotensin-aldosterone system in a substudy (n = 805). Plasma renin activity increased with valsartan (54%-73%) and decreased with nebivolol (51%-65%) and the combination treatment (17%-39%). Plasma aldosterone decreased with individual treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
1
14
0
1
Order By: Relevance
“…Indeed, ACE-i and ARB tend to lower aldosterone concentrations, but increase PRA, while beta-blockers might lower both, and MRA increase both. 31 37 Although none of the patients included in this study were taking an angiotensin receptor blocker-neprilysin inhibitor (ARNI), in light of the new HF guidelines it may be interesting to point out that previous studies have demonstrated that the association of sacubitril, a neprilysin inhibitor, does not affect PRA or serum aldosterone concentration. 38 , 39 Hypertensive patients treated with neurohormonal blockers demonstrate increased PRA and plasma aldosterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ACE-i and ARB tend to lower aldosterone concentrations, but increase PRA, while beta-blockers might lower both, and MRA increase both. 31 37 Although none of the patients included in this study were taking an angiotensin receptor blocker-neprilysin inhibitor (ARNI), in light of the new HF guidelines it may be interesting to point out that previous studies have demonstrated that the association of sacubitril, a neprilysin inhibitor, does not affect PRA or serum aldosterone concentration. 38 , 39 Hypertensive patients treated with neurohormonal blockers demonstrate increased PRA and plasma aldosterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…A substudy conducted within the NAC-MD-01 trial ( N = 805) examined patients’ BP using ambulatory BP monitoring (ABPM) and their levels of PRA and plasma aldosterone [ 80 ]. Those examinations revealed that at Week 8, the SPC 10/160 was significantly more effective in lowering ABPM than the component monotherapies valsartan 160 (SBP/DBP; P < 0.001, both) and Neb 10 (DBP; P < 0.01); in addition, the SPC 20/320 reduced 24-h DBP and SBP significantly more than valsartan 320 ( P < 0.01, both) but not Neb 40.…”
Section: Effects On Blood Pressure and Biomarkers In Patients With Hymentioning
confidence: 99%
“…4 b). A post-hoc analysis with pooled active treatment groups demonstrated a significant correlation between 24-h, daytime, and nighttime ABPM reduction and baseline PRA in participants treated with Neb and SPCs, but not with valsartan; baseline aldosterone levels were correlated with 24-h, daytime, and night-time ABPM reduction in those treated with the SPCs, but not with the monotherapies [ 80 ].…”
Section: Effects On Blood Pressure and Biomarkers In Patients With Hymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this aberration, the nebivolol/valsartan SPC was still more effective than placebo in this group . In spite of nominal reductions in aldosterone levels, especially with the SPCs, aldosterone breakthrough—a phenomenon that affects approximately 30% of individuals receiving RAAS inhibitors—could occur with longer nebivolol‐valsartan treatment. The duration of this study did not allow for this assessment.…”
Section: Study Limitationsmentioning
confidence: 89%